Stroke after Varicella-Zoster Infection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers at University Hospitals of Ferrara and Padova, Italy, report a case of cerebral infarction and stroke occurring 3 months after varicella-zoster virus (VZV) infection in a 5-year-old immunocompetent child, and they provide a literature review of 70 similar cases.